DAPSONE-INDUCED TOXIC MACULOPATHY IN LEPROSY PATIENT - Ayuningtyas, Sita Paramita; Djatikusumo, Ari; Nusanti, Syntia; Dewiputri, Salmarezka; Sidik, Mohamad (International Journal of Retina, 2023)
Introduction: Dapsone has been widely used as a part of multidrug therapy for leprosy patients. Ocular side effects are rare. Ocular toxicity manifestations include retinal necrosis, optic atrophy, macular infarction, bilateral exudative retinal detachment, and choroidal detachment. We reported a rare case of dapsone-induced toxic maculopathy in a leprosy patient. Case Report: A 32-year-old male complained of blurred vision and a gray spot in central vision in the left eye (LE) for one month prior to admission. He had been treated with multidrug therapy (MDT) for leprosy for seven months. The MDT consists of dapsone, clofazimine, and rifampicin. The best-corrected visual acuity (BCVA) of the right eye (RE) and the LE were 6/6 and 6/12, respectively. A funduscopy of the LE showed decreased macular reflex. A color vision defect following the tritan axis was found in the LE. The Humphrey visual field (HVF) test of the LE revealed a central scotoma. Macular optical coherence tomography (OCT) showed intraretinal hyperreflectivity and subretinal fluid. Dapsone was then stopped in collaboration with a dermatologist. Two months after the discontinuation of Dapsone, the BCVA of the LE improved to 6/7.5, then 6/6 three months later. Color vision, macular OCT, and HVF tests revealed improvements. Multifocal ERG of both eyes (BE) also showed improvement in N1 and P1 wave amplitude in both eyes on 9-month follow-up after dapsone discontinuation. Discussion: Instead of direct drug toxicity, the mechanism of ocular side effects is thought to be ischemia caused by two distinct mechanisms. Macular ischemia is caused by acute, severe peripheral hypoxia and the physical effect of red cell fragmentation due to the hemolytic process. After discontinuation of dapsone, this case showed improvement in visual function and macular structure. Conclusion: Toxic maculopathy may be present in leprosy patients receiving dapsone treatment, although it is uncommon. Regular follow-up and evaluation of visual function and macular involvement are essential. Early detection of dapsone-induced toxic maculopathy and prompt discontinuation of dapsone may result in an improvement of visual functions.